Development of sensors, probes and imaging techniques for pollutant monitoring in geo-environmental model tests. Issue 4 (December 2001) - Lynch, R. J.; Allersma, H.; Barker, H.; Bezuijen, A.; Bolton, M. D.; Cartwright, M.; Davies, M. C. R.; Depountis, N.; Esposito, G.; Garnier, J.; Garrett, J. L. L. De Almeida; Harris, C.; et al.
Abstract : In order to be able to track the movement of pollutant plumes during geotechnical centrifuge and other geo-environmental experiments, a number of techniques have been investigated: fibre-optic photometric sensors, resistivity probes, resistivity tomography, and copper ion-selective electrodes. Methods of image analysis, signal processing techniques and multi-spectral image analysis were also explored and applied to images of moving plumes. In addition, an optical technique for detecting NAPL by cone probe was investigated. Their relative merits are discussed. This work was conducted as part of an EU-funded network programme: NECER (Network of European geotechnical Centrifuges for Environmental Research), and this paper summarises the conclusions of the sensors and imaging working group.